A pyridine vanadium complex modified sodium metal negative electrode and preparation method thereof
By coating the pyridine vanadium complex on the sodium metal surface, the problem of dendrites growing during the electroplating/stripping process is solved, and the effect of improving the cycle stability and cycle life of the battery is achieved.
Patent Information
- Application Number
- CN202211090946.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-07
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2042-09-07
AI Technical Summary
The sodium metal negative electrode is prone to dendrites during the electroplating/peeling process, resulting in short circuits. The uniformity and mechanical strength of the existing interface film are insufficient, making it difficult to effectively inhibit dendrites' growth.
The artificial SEI layer is constructed by coating the pyridine vanadium complex on the sodium metal surface. Through the ease of reduction of pyridine groups and the high sodium philtrum of vanadium nitrogen alloy, sodium ion adsorption and uniform deposition are induced, thereby improving the mechanical strength and stability of the SEI layer.
It effectively inhibits the growth of sodium dendrites, improves the cycle stability and cycle life of sodium metal batteries, and reduces side reactions and electrolyte consumption during electroplating/stripping.
Smart Images

Figure CN116111047B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of sodium metal batteries, and more specifically, relates to a method for modifying a sodium metal negative electrode using a pyridine vanadium complex and performance optimization. Background Art
[0002] People's demand for electronic products in life is increasing day by day. Lithium-ion batteries, as the main power source for current electronic products, are widely used due to their high energy density and power density. However, the shortage, uneven distribution and high price of lithium resources restrict the large-scale application of lithium batteries. Sodium and lithium belong to the same main group and have similar electrochemical properties. Using sodium as a negative electrode to replace lithium has the advantages of low cost and abundant reserves. Sodium-ion battery negative electrode materials generally use titanium-based materials, carbon-based materials, organic materials and alloy materials. Among the many sodium-ion battery negative electrode materials, the sodium metal negative electrode has a high theoretical specific capacity (1166mA hg -1 ) and low redox potential (-2.71 V vs. standard hydrogen electrode potential) and is considered to be the most promising negative electrode material.
[0003] Sodium metal is highly active. When used as a sodium metal anode, it easily reacts with carbonate electrolytes to form a loose and porous solid electrolyte interphase (SEI). The volume expansion of the sodium metal negative electrode during the charge and discharge cycle is large, which can easily cause the SEI film to crack, and the fresh sodium metal is re-exposed to the electrolyte, further consuming the sodium source and the electrolyte, resulting in a decrease in the Coulomb efficiency of the subsequent electroplating / stripping process. In addition, the uneven charge distribution on the surface of sodium metal causes tiny dendrites to appear in the sodium ion-rich area after the initial cycle. The dendrites continue to grow and eventually pierce the diaphragm, causing a short circuit. The current ways to inhibit the growth of sodium dendrites mainly include constructing a three-dimensional structured current collector, an artificial interface layer, and a self-healing electrostatic shielding layer. For example, Chinese patent application number CN202111039647.1 discloses an alkali metal negative electrode protected by a boron oxide interface film. The patent uses a boric acid solution to react with an alkali metal to form a composite protective layer in situ on the surface of the alkali metal negative electrode. The composite protective layer promotes the conduction of alkali metal ions and induces the uniform deposition of alkali metal ions on the negative electrode surface. However, the interface film is mainly formed by spontaneous reaction between alkali metal and electrolyte, with poor uniformity and mechanical strength. It is easy to break during the electroplating stripping process, exposing fresh alkali metal to the electrolyte again, further causing side reactions to consume electrolyte and sodium, reducing specific capacity, and with the increase of SEI layer thickness, alkali metal ions are difficult to diffuse, resulting in poor battery cycle performance and rate performance.
[0004] In contrast, the artificial SEI layer not only has good ion conductivity, which can alleviate the local enrichment of sodium ions and facilitate the uniform deposition of sodium ions, but also has high mechanical strength, which can effectively inhibit the growth of sodium dendrites and improve the battery cycle stability. Summary of the invention
[0005] In order to achieve the above-mentioned object, the present invention constructs an artificial SEI layer by coating a pyridine vanadium complex on the surface of sodium metal, aiming to suppress the problem of sodium metal easily generating dendrites during the electroplating stripping process, and provides a modified sodium metal negative electrode and a preparation method thereof. The artificial SEI layer constructed by the present invention has the advantages of simple method, low cost, high mechanical strength, good uniformity, few side reactions, excellent electrochemical performance, etc.
[0006] To achieve the above-mentioned purpose of the invention, the first purpose of the present invention is to provide a modified sodium metal negative electrode material, which is obtained by modifying the surface of sodium metal with a pyridine vanadium complex, and the mass ratio of the pyridine vanadium complex to sodium metal is 1:3-1:6.
[0007] The pyridine vanadium complex is preferably one of vanadium pyridine carboxylate, vanadium pyridine dicarboxylate, vanadium pyridine imine, or a combination thereof.
[0008] The second object of the present invention is to provide a method for preparing a modified sodium metal negative electrode material, the specific preparation steps are:
[0009] (1) rolling a sodium metal block into a rectangular nano-metal sheet;
[0010] (2) a certain amount of pyridine vanadium complex powder is placed in a glove box and fully ground, then coated on a rectangular sodium metal sheet and reacted;
[0011] (3) After the reaction is completed, an artificial interface film is formed on the surface of the rectangular sodium metal sheet, and a pyridine vanadium complex modified sodium metal negative electrode material is obtained.
[0012] The rectangular sodium metal flakes have a size of 5 cm in width, 8-12 cm in length, and a thickness of 200-400 nm; the pyridine vanadium complex powder is ground for 15-60 min and used in an amount of 40-80 mg. After coating, the powder is left aside for 10-24 h to allow a spontaneous reaction to occur.
[0013] The third object of the present invention is to provide a button-type symmetrical battery comprising a positive electrode, a negative electrode and an electrolyte.
[0014] The negative electrode is obtained by cutting the above-mentioned pyridine vanadium complex modified sodium metal negative electrode material into original sheets with a diameter of 10 mm;
[0015] The electrolyte is 1M NaClO4-EC / DEC / 5% FEC, which is obtained by dissolving 1 mole of sodium perchlorate in solvent ethyl carbonate (EC), solvent diethyl carbonate (DEC) and additive fluoroethyl carbonate (FEC).
[0016] Furthermore, the volume ratio of EC to DEC in the electrolyte is 1:1, the amount of additive FEC added is 5%, and the amount of electrolyte used is 200 μL.
[0017] The present application applies a pyridine vanadium complex to the surface of a sodium metal negative electrode to construct an artificial SEI layer. The pyridine group in this type of compound, as a "π-deficient heterocycle", has the characteristics of being difficult to oxidize and easy to reduce, and is easily reduced to olefin organic matter by sodium, and the N atom on the pyridine ring can coordinate with the metal vanadium ion to form a vanadium-nitrogen alloy with high sodium affinity, inducing the adsorption of sodium ions. After the pyridine vanadium complex is uniformly coated on the surface of sodium metal, it reacts with sodium to form an inorganic compound sodium salt and an organic compound in situ. The inorganic component can effectively improve the mechanical strength of the SEI layer, and the artificial interface layer containing organic compounds can effectively protect the sodium metal negative electrode from being corroded by the electrolyte. While effectively inhibiting the growth of dendrites, the cycle life of the sodium metal battery is improved. In addition, the method of physical coating to construct an artificial SEI layer adopted in the present application has the advantages of simple operation and low cost, and is convenient for large-scale production.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] (1) The inventors of the present invention creatively coated a pyridine vanadium complex containing an organic functional group and a metallic element vanadium on the surface of sodium metal. The modified sodium metal negative electrode material obtained after the reaction of the pyridine vanadium complex and sodium metal has an inorganic compound with high hardness and an organic compound with high adjustability. The synergistic effect of the two can not only effectively protect the sodium metal negative electrode from electrolyte corrosion, but also improve the mechanical strength of SEI, effectively inhibit the growth of sodium dendrites, and enhance the cycle stability of the sodium metal battery during the charge and discharge process.
[0020] (2) The method for preparing the sodium metal negative electrode material modified by the pyridine vanadium complex of the present invention is to uniformly coat the pyridine vanadium complex on the surface of the sodium metal by simple physical means, which has the advantages of simple operation and low cost and is convenient for large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] (1) Figure 1 This is a comparison diagram before and after coating the sodium metal surface with vanadyl picolinate in Example 1 of the present invention, A is pure sodium, and B is vanadyl picolinate coated on the sodium metal surface;
[0022] (2) Figure 2The X-ray photoelectron spectroscopy (XPS) graph of C1s, O 1s, N 1s and Na 1s of the sodium sheet coated with vanadyl picolinate in Example 1 of the present invention;
[0023] (3) Figure 3 The sodium sheets obtained by coating pyridine carboxylic acid vanadyl in Example 1 of the present invention were assembled into a symmetrical battery and then tested at 0.5 mA cm -2 Current density and capacity are 1 mAh cm -2 The time voltage diagram below;
[0024] (4) Figure 4 The sodium sheets obtained by coating vanadium pyridine dicarboxylate in Example 2 of the present invention were assembled into a symmetrical battery and then tested at 0.5 mA cm -2 Current density and capacity are 1 mAh cm -2 The time voltage diagram below;
[0025] (5) Figure 5 The sodium sheets obtained by coating vanadium pyridine imine in Example 3 of the present invention were assembled into a symmetrical battery and then tested at 0.5 mA cm -2 Current density and capacity are 1 mAh cm -2 The time voltage diagram below;
[0026] (6) Figure 6 The sodium sheets obtained by coating pyridine carboxylic acid vanadyl and pyridine dicarboxylic acid vanadium in Example 4 of the present invention were assembled into a symmetrical battery and then tested at 0.5 mA cm -2 Current density and capacity are 1 mAh cm -2 The time voltage diagram below. DETAILED DESCRIPTION
[0027] In order to further understand the content of the present invention, the present invention is now described in detail in conjunction with specific embodiments.
[0028] Example 1
[0029] Weigh 40 mg of pyridine carboxylic acid vanadyl powder, grind it carefully in a glove box for 60 minutes, and evenly coat it on the surface of a rectangular sodium sheet with a width of 5 cm, a length of 8 cm, and a thickness of 200 nm to construct an artificial SEI layer. The sodium sheet was then placed in a glove box for 24 hours. After the reaction, the sodium sheet was cut into 10 mm discs and used as positive and negative electrodes to assemble button symmetrical batteries. The electrolyte used in the battery was 1M NaClO4-EC / DEC / 5% FEC, and the amount used was 200 μL. After assembly, the button battery was placed at a current density of 0.5 mA cm -2 , with a capacity of 1 mAh cm -2 The battery was operated under the conditions of , and its cycle stability during charge and discharge was tested.
[0030] Figure 1This is a comparison of the original sodium sheet and the sodium sheet coated with vanadyl picolinate. The original sodium metal surface has a metallic luster. After being coated with the blue vanadyl picolinate powder, the color of the sodium metal surface changes from silver gray to black, indicating that a chemical reaction occurs after coating with vanadyl picolinate.
[0031] Figure 2 The XPS spectra of C 1s, O 1s, N 1s and Na 1s after vanadyl picolinate was coated on the surface of sodium metal. The results show that vanadyl picolinate decomposes and reacts with sodium to form the organic compound sodium methacrylate (NaOC(O)CCH3CH2) and the inorganic compound sodium carbonate and vanadium nitrogen alloy. The organic compound in SEI can effectively protect the sodium metal negative electrode from electrolyte corrosion, while the inorganic compound sodium carbonate dispersed in SEI can effectively improve the mechanical strength of SEI. In addition, vanadium nitrogen alloy can induce sodium ion adsorption and promote the uniform deposition of sodium ions.
[0032] Figure 3 The time-voltage diagram of the modified sodium metal disc obtained in the present invention after being used as the positive and negative electrodes to assemble a symmetrical battery. -2 Current density and capacity are 1 mAh cm -2 It was found that the overpotential was reduced from 150mV to 100mV compared with pure sodium, and the cycle life was extended from 120h to more than 300h. This shows that coating pyridine carboxylic acid vanadium oxypowder to construct an artificial SEI layer not only promotes the uniform deposition of sodium ions, but also inhibits the growth of sodium dendrites, improves the stability of SEI, and thus extends the cycle life of the battery.
[0033] Example 2
[0034] Weigh 80 mg of vanadium pyridine dicarboxylate powder, grind it carefully in a glove box for 25 minutes, and then evenly coat it on the surface of a sodium sheet with a width of 5 cm, a length of 12 cm, and a thickness of 400 nm to construct an artificial SEI layer. The sodium sheet was then placed in a glove box for 10 hours. After the reaction, the sodium sheet was cut into 10 mm discs and used as positive and negative electrodes to assemble a button symmetrical battery. The electrolyte used in the battery was 1M NaClO4-EC / DEC / 5% FEC, and the amount used was 200 μL. After assembly, the button battery was charged at a current density of 0.5 mA cm -2 , with a capacity of 1 mAh cm -2 The battery was operated under the conditions of , and its cycle stability during charge and discharge was tested.
[0035] Figure 4 The modified sodium metal discs obtained by coating with vanadium dipicolinate were subjected to the conditions of 0.5 mA cm -2 Current density and capacity are 1 mAh cm -2The time-voltage diagram obtained under the conditions of operation shows that the overpotential is reduced from 150mV to 100mV compared with pure sodium, and the cycle life is extended from 120h to more than 240h.
[0036] Example 3
[0037] Weigh 60 mg of pyridine imine vanadium powder, grind it carefully in a glove box for 15 minutes, and evenly coat it on the surface of a sodium sheet with a width of 5 cm, a length of 10 cm, and a thickness of 300 nm to construct an artificial SEI layer. The sodium sheet was then placed in a glove box for 16 hours. After the reaction, the sodium sheet was cut into 10 mm discs and used as positive and negative electrodes to assemble a button symmetrical battery. The electrolyte used in the battery was 1M NaClO4-EC / DEC / 5% FEC, and the amount used was 200 μL. After assembly, the button battery was charged at a current density of 0.5 mA cm -2 , with a capacity of 1 mAh cm -2 The battery was operated under the conditions of , and its cycle stability during charge and discharge was tested.
[0038] Figure 5 The modified sodium metal discs coated with vanadium pyridine imide were subjected to 0.5 mA cm -2 Current density and capacity are 1 mAh cm -2 The time-voltage diagram obtained under the conditions of operation shows that the overpotential is reduced from 150mV to 100mV compared with pure sodium, and the cycle life is extended from 120h to more than 400h.
[0039] Example 4
[0040] Weigh 30 mg of vanadium pyridine carboxylate and 30 mg of vanadium pyridine dicarboxylate powder, grind them carefully in a glove box for 40 minutes, and evenly coat them on the surface of a sodium sheet with a width of 5 cm, a length of 11 cm, and a thickness of 300 nm to construct an artificial SEI layer. The sodium sheet was then placed in a glove box for 20 hours. After the reaction, the sodium sheet was cut into 10 mm discs and used as positive and negative electrodes to assemble button symmetrical batteries. The electrolyte used in the battery is 1M NaClO4-EC / DEC / 5% FEC, and the amount used is 200 μL. After assembly, the button battery is placed at a current density of 0.5 mA cm -2 , with a capacity of 1 mAh cm -2 The battery was operated under the conditions of , and its cycle stability during charge and discharge was tested.
[0041] Figure 6 The modified sodium metal discs obtained by coating with vanadyl picolinate and vanadium dipicolinate were subjected to the conditions of 0.5 mA cm -2 Current density and capacity are 1 mAh cm -2The time-voltage diagram obtained under the conditions of operation shows that the overpotential is reduced from 150mV to 100mV compared with pure sodium, and the cycle life is extended from 120h to more than 350h.
Claims
1. A modified sodium metal negative electrode material, characterized in that: The modified sodium metal negative electrode material is obtained by modifying the surface of the sodium metal with a pyridine vanadium complex, wherein the mass ratio of the pyridine vanadium complex to the sodium metal is 1:3-1:6; the pyridine vanadium complex is one of pyridine carboxylic acid vanadium, pyridine dicarboxylic acid vanadium, pyridine imine vanadium or a combination thereof; the specific preparation steps of the modified sodium metal negative electrode material are: (1) rolling a sodium metal block into a rectangular nano-metal sheet; (2) a certain amount of pyridine vanadium complex powder is placed in a glove box and fully ground, then coated on a rectangular sodium metal sheet and reacted; (3) After the reaction is completed, an artificial interface film is formed on the surface of the rectangular sodium metal sheet, and a modified sodium metal negative electrode material is obtained.
2. A method for preparing the modified sodium metal negative electrode material according to claim 1, characterized in that: The specific preparation steps are: (1) rolling a sodium metal block into a rectangular nano-metal sheet; (2) a certain amount of pyridine vanadium complex powder is placed in a glove box and fully ground, then coated on a rectangular sodium metal sheet and reacted; (3) After the reaction is completed, an artificial interface film is formed on the surface of the rectangular sodium metal sheet, and a modified sodium metal negative electrode material is obtained.
3. The method for preparing the modified sodium metal negative electrode material according to claim 2, characterized in that: The rectangular sodium metal flakes have a size of 5 cm in width, 8-12 cm in length, and a thickness of 200-400 nm; the pyridine vanadium complex powder is ground for 15-60 min and used in an amount of 40-80 mg. After coating, the powder is left aside for 10-24 h to allow a spontaneous reaction to occur.
4. A button-type symmetrical battery, characterized in that: The battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode is obtained by cutting the modified sodium metal negative electrode material obtained by the preparation method of the modified sodium metal negative electrode material according to claim 1 or any one of claims 2 to 3 into original sheets with a diameter of 10 mm.
5. The symmetrical battery according to claim 4, characterized in that: The electrolyte is 1MNaClO4-EC / DEC / 5%FEC, which is obtained by dissolving 1 mole of sodium perchlorate in solvent ethyl carbonate (EC), solvent diethyl carbonate (DEC) and additive fluoroethyl carbonate (FEC); The volume ratio of EC to DEC in the electrolyte is 1:1, the amount of additive FEC added is 5%, and the amount of electrolyte used is 200 μL.
Citation Information
Patent Citations
Alkali metal negative electrode protected by boron-oxygen interface film, and preparation method and application thereof
CN113948676A
Anode material for lithium ion battery and preparation method thereof
CN102044674A
Alkali metal negative electrode with stable circulation, preparation method thereof and alkali metal battery
CN114975897A